2019
DOI: 10.1080/14737167.2019.1647104
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and cost-effectiveness of infliximab as first-line treatment in rheumatoid arthritis: systematic review and meta-analysis

Abstract: Introduction: Early biological treatment of rheumatoid arthritis (RA) may reverse the autoimmune response in some patients resulting in favorable long-term outcomes. Although the cost-effectiveness of this strategy has been questioned, biosimilar entries warrant the revision of clinical and pharmaco-economic evidence. Areas covered: We conducted a systematic review of randomized controlled trials (RCTs) published up to 24 May 2018 in Pubmed, EMBASE and Cochrane CENTRAL, comparing infliximab with non-biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…IL-6 and TNF are key pro-inflammatory cytokines implicated in neutrophilia, extracellular matrix production and chronic inflammation during severe asthma. In spite of possible side effects, TNF neutralization is a golden standard in treating rheumatoid arthritis, psoriasis and inflammatory bowel disease therapy ( 100 ). Anti-IL-6 drugs are also approved in RA ( 101 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and TNF are key pro-inflammatory cytokines implicated in neutrophilia, extracellular matrix production and chronic inflammation during severe asthma. In spite of possible side effects, TNF neutralization is a golden standard in treating rheumatoid arthritis, psoriasis and inflammatory bowel disease therapy ( 100 ). Anti-IL-6 drugs are also approved in RA ( 101 ).…”
Section: Discussionmentioning
confidence: 99%
“…39 Infliximab is a TNF inhibitor approved for the treatment of moderate-tosevere RA in the United States of America since 1999. 40 In particular, IFX, which is a human-mouse chimeric monoclonal antibody, can rapidly bind to TNF-α with high affinity in both soluble and permeable forms, resulting in the generation of stable complexes and thus inhibiting the binding of TNF-α to receptors and depriving its biological activity. In addition, both in vitro and in vivo experiments have shown that in cells expressing the permeable form of TNF-α, it could be dissolved following binding to IFX.…”
Section: Infliximab-loaded Hydrogel Alleviated Painmentioning
confidence: 99%
“…In addition, both in vitro and in vivo experiments have shown that in cells expressing the permeable form of TNF-α, it could be dissolved following binding to IFX. [40][41][42] Herein, administration of HG-IFX was shown to reduce inflammation by directly inhibiting TNF-α, thereby downregulating the expression of a series of pain-related inflammatory cytokines (eg, IL-1β, IL-6, and IL-17) and alleviating the pain symptoms of RA.…”
Section: Infliximab-loaded Hydrogel Alleviated Painmentioning
confidence: 99%
“…The patients treated with infliximab demonstrate a significant reduction of adhesion molecules, including IL-8, IL-6, MCP-1, and IL-1. Despite the safety profile, the infliximab exhibits severe adverse effects such as reactivation of tuberculosis or hepatitis B, cancers, and lymphoma [47]. Adalimumab is another example of a TNF-alpha inhibitor, a wholly humanized antibody, and administered through a subcutaneous route.…”
Section: Current Conventional Therapies Against Ra and Associated Promentioning
confidence: 99%